Using dune restoration on an urban beach as a coastal resilience approach - Johnston, Karina K.; Dugan, Jenifer E.; Hubbard, David M.; Emery, Kyle A.; Grubbs, Melodie W. (Frontiers in Marine Science, 2023)
Coastal dunes are globally recognized as natural features that can be important adaptation approaches for climate change along urban and natural shores. We evaluated the recovery of coastal dunes on an intensively groomed urban beach in southern California over a six-year period after grooming was discontinued. Restoration actions were minimal and included installation of three sides of perimeter sand fencing, cessation of mechanical grooming and driving, and the addition of seeds of native dune plants. To track recovery, we conducted physical and biological surveys of the restoration site and an adjacent control site (groomed beach) using metrics including sand accretion, elevation, foredune and hummock formation, vegetation recovery, and wildlife use. Sediment accretion, elevation, and geomorphic complexity increased over time in the restoration site, largely in association with sand fencing and dune vegetation. A foredune ridge (maximum elevation increase of 0.9 m) and vegetated hummocks developed, along with a general increase in elevation across the restoration site (0.3 m). After six years, an estimated total volume of approximately 1,730 m3 of sand had accreted in the restoration site and 540 m3 of sand had accreted in the foredune ridge. Over the same period, more than a meter of sediment (vertical elevation change) accumulated along the perimeter sand fencing. Groomed control areas remained flat and uniform. The total cover of vegetation in the restoration site increased over time to a maximum of approximately 7% cover by the sixth year. No vegetation was observed on the groomed control site. Native plant species formed distinct zones across the restoration site beginning by the second year and increasing over time, with dune forming species aggregating closest to the ocean in association with the incipient foredune ridge. Ecological functions observed in the restoration area included presence of dune invertebrates, shorebird roosting, and use by a breeding federally threatened shorebird, the western snowy plover (Charadrius nivosus nivosus). Our findings on geomorphic and ecological responses of a pilot dune restoration on a heavily groomed urban beach provide new insights on the opportunities and expectations for restoring dunes as nature-based solutions for climate adaptation on urban shorelines.